Sodobne aplikacije teorije racionalne izbire na področju sociologije religije - Lavrič, Miran (Družboslovne razprave, 2007)
The article is formulated as a short overview of the main theses of sociological rational choice theory which has recently also been successfully applied to the area of the sociology of religion. This relatively young approach to religious research (also) considers religious behaviour as being predominantly rationally motivated. It is assumed that individuals make their decisions with regard to their religiosity in the same way as they make other decisions in life, that is, by weighing up the costs and benefits and negotiating in their exchange with supernatural agents. Basic approaches and assumptions of key authors in the area are presented.
Keywords: religija; religion; religiosity; religioznost; sociološke teorije; teorija racionalne izbire